Bahasa Inggris Bahasa Inggris - Krisna Nopiyanti; Hardjanto; Eva Rachmawati (Postgraduate, University of Mataram, 2025)
The role of stakeholders is a crucial factor in tourism development. Tourism development cannot be carried out solely by area managers but requires support and contributions from various stakeholders. This study aims to analyze stakeholder involvement in managing Mangrove Sari Ecotourism. This study involved interviews, field observations, and literature reviews, and a qualitative analysis approach was applied. The researchers conducted a stakeholder analysis to identify, classify, and map the roles of each party. The analysis identified eight stakeholders involved in managing Mangrove Sari Ecotourism. The stakeholder in the key player (strong influence and high importance) is Mangrove Sari Tourism Awareness Group. The stakeholders in context setters (strong interest but low influence) are Kaliwlingi Village Government, Mangrove Sari Coastal Forest Conservation Community Group, and Brebes Regency Culture and Tourism Office. The stakeholder in the subject (strong influence but low interest) is the Youth Group Kaliwlingi Village. The stakeholders in Crowds (low interest and low influence) are Forestry Service Branch Region V, Brebes Regency Marine and Fisheries Service, and Kaliwlingi Sea Guardian Community Group. Stakeholder relations remain suboptimal due to role limitations and potential conflicts, which hinder effective coordination and affect the management of Mangrove Sari ecotourism.